How does playfulness (re)frame the world? Evidence for selective cognitive and behavioral redirecting in times of adversity - Shen, Xiangyou; Crawley, Zoe (Frontiers in Psychology, 2025)
Do playful people perceive, approach, and respond to their environment and life events differently than less playful individuals? This study examined playfulness as a perceptual lens and its potential broader (re)framing effects spanning cognition, emotion, and behavior in the disruptive pandemic context. Comparing two groups with contrasting levels of playfulness derived from a nationwide US adult sample (n = 503), we found evidence for a selective (re)framing effect resembling a "color spotlight" rather than "rose-tinted" glasses. Highly playful individuals exhibited an optimistic future outlook while maintaining realistic perceptions of current situations. They engaged in higher levels of resilient coping and adaptive leisure, instigating behavioral redirection beyond perceptual (re)framing when encountering adversity, while experiencing more immersion, activeness, and positive affect in daily activities. This evidence reveals "lemonading"-creatively imagining and pursuing positive possibilities-as the core of playful redirection, supporting playfulness' potential to build resilience. Our findings advance a nuanced understanding of the playful (re)framing effect and its boundary conditions, emphasizing cognitive and behavioral redirection in shaping experiences. This study underscores the importance of (1) cultivating playfulness as a character strength and resilience factor, and (2) examining the experiential quality of playful engagement as key to unlocking its transformative potential across life domains.